Universal Health Coverage in Bangladesh: Activities, Challenges, and Suggestions. (3rd March 2019) - Joarder, Taufique; Chaudhury, Tahrim Z.; Mannan, Ishtiaq
Abstract : Catastrophic health expenditure forces 5.7 million Bangladeshis into poverty. Inequity is present in most of health indicators across social, economic, and demographic parameters. This study explores the existing health policy environment and current activities to further the progress towards Universal Health Coverage (UHC) and the challenges faced in these endeavors. This qualitative study involved document reviews (n=22) and key informant interviews (KII, n=15). Thematic analysis of texts (themes: activities around UHC, implementation barriers, suggestions) was done using the manual coding technique. We found that Bangladesh has a comprehensive set of policies for UHC, e.g., a health-financing strategy and staged recommendations for pooling of funds to create a national health insurance scheme and expand financial protection for health. Progress has been made in a number of areas including the roll out of the essential package of health services for all, expansion of access to primary health care services (support by donors), and the piloting of health insurance which has been piloted in three subdistricts. Political commitment for these areas is strong. However, there are barriers pertaining to the larger policy level which includes a rigid public financing structure dating from the colonial era. While others pertain to the health sector's implementation shortfalls including issues of human resources, political interference, monitoring, and supervision, most key informants discussed demand-side barriers too, such as sociocultural disinclination, historical mistrust, and lack of empowerment. To overcome these, several policies have been recommended, e.g., redesigning the public finance structure, improving governance and regulatory mechanism, specifying code of conduct for service providers, introducing health-financing reform, and collaborating with different sectors. To address the implementation barriers, recommendations include improving service quality, strengthening overall health systems, improving health service management, and improving monitoring and supervision. Addressing demand-side barriers, such as patient education and community empowerment, is also needed. Research and advocacy are required to address crosscutting barriers such as the lack of common understanding of UHC.